Physical, mechanical, and morphological properties of treated sugar palm/glass reinforced poly(lactic acid) hybrid composites - Shah Faisal Khan, Sherwani; Zainudin, Edi Syams; Salit, Mohd Sapuan; Leman, Zulkiflle; Abdan, Khalina (MDPI AG, 2021)
This research was performed to evaluate the physical, mechanical, and morphological properties of treated sugar palm fiber (SPF)/glass fiber (GF) reinforced poly(lactic acid) (PLA) hybrid composites. Morphological investigations of tensile and flexural fractured samples of composites were conducted with the help of scanning electron microscopy (SEM). Alkaline and benzoyl chloride (BC) treatments of SPFs were performed. A constant weight fraction of 30% total fiber loading and 70% poly(lactic acid) were considered. The composites were initially prepared by a Brabender Plastograph, followed by a hot-pressing machine. The results reported that the best tensile and flexural strengths of 26.3 MPa and 27.3 MPa were recorded after alkaline treatment of SPF, while the highest values of tensile and flexural moduli of 607 MPa and 1847 MPa were recorded after BC treatment of SPF for SPF/GF/PLA hybrid composites. The novel SPF/GF/PLA hybrid composites could be suitable for fabricating automotive components.